Implementasi Program Simpan Pinjam Kelompok Perempuan Di Kecamatan Muara Lakitan Kabupaten Musi Rawas - Austin, Trecy (Jurnal Publisitas, 2020)
The research titled Implementation of Women's Lending and Saving Program Program in Muara Lakitan Sub-district of Musi Rawas Regency aims to explain the implementation of Women's Lending Program Group, timely and late group groups and to identify factors that support the Program. Based on Ripley and Franklin's theory, there are three factors that influence the success of policy implementation, such as the dimension of compliance level, smoothness of routine and absence of problems, past performance and impact. This research according to data type used is mix method research, sequential explanatory strategy, with the population is poor housewife using SPP revolving fund. Samples of the research were 95 respondents of the group on time and late which spread in 15 village. Based on observations and interviews, the delay in fund disbursement was caused by the number of Verification Team executors only 1 person. In addition, the means of transportation used by the Private Verification Team without the assistance of accommodation during the disbursement of funds in Lubuk Linggau. Some respondents claimed that they were not supervised by the executor during the business because they already have a business with a good enough income, which never experienced delinquency. Obstacles in loan repayment due to fluctuating monthly income. However, this barrier can be overcome by the UPK in the District. Further factors supporting the success of program implementation in Muara Lakitan are Compliance executor and membe, capability of group implementer of borrower, and also community participation.